Corrigendum to “Effects of different laser wavelengths on process performance and weld seam properties in copper processing for electric vehicle applications” [Opt. Laser Technol. 191 (2025) 113274](S0030399225008655)(10.1016/j.optlastec.2025.113274) - Kaufmann, Florian; Hentschel, Oliver; Roth, Stephan; Schmidt, Michael (Optics and Laser Technology, 2025)
The authors regret that revisions were necessary in some of the article. [PDF page 19] “Data availability”, “Ethics approval”, “Consent to participate” and “Consent for publication” are not set to headings-format like “Funding”. “Declarations” should be deleted entirely, and there should be no dots after “Data availability” and “Consent to participate” as these are headings. On PDF page 4 (middle, right, 2x) and PDF page 8 (middle, left), there are mistakenly three minus signs (“–––”): page 4 “0.5–––8 kW” should read “0.5 – 8 kW” and “2–––20 m/min” should read “2 – 20 m/min” and page 8 “7000–––9000 W/mm” should read "7000 – 9000 W/mm". The authors would like to apologise for any inconvenience caused.
CRIS-Team Scopus Importer:2025-07-04